2023
DOI: 10.1111/nph.19358
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between beech and oak seedlings can modify the effects of hotter droughts and the onset of hydraulic failure

Eugénie Mas,
Hervé Cochard,
Janisse Deluigi
et al.

Abstract: Summary Mixing species with contrasting resource use strategies could reduce forest vulnerability to extreme events. Yet, how species diversity affects seedling hydraulic responses to heat and drought, including mortality risk, is largely unknown. Using open‐top chambers, we assessed how, over several years, species interactions (monocultures vs mixtures) modulate heat and drought impacts on the hydraulic traits of juvenile European beech and pubescent oak. Using modeling, we estimated species interaction effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 98 publications
1
5
0
Order By: Relevance
“…In an article published in this issue of New Phytologist , Mas et al . (2024; 1021–1034) deepen our understanding of how species interactions might mitigate future hot drought effects. Mas et al .…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…In an article published in this issue of New Phytologist , Mas et al . (2024; 1021–1034) deepen our understanding of how species interactions might mitigate future hot drought effects. Mas et al .…”
Section: Figmentioning
confidence: 99%
“…Given the damages already seen during hotter droughts with higher VPD, it is essential that we identify how individual species and ecosystems will respond to hotter droughts in the future. In an article published in this issue of New Phytologist, Mas et al (2024; 1021-1034 deepen our understanding of how species interactions might mitigate future hot drought effects. Mas et al demonstrate how hot drought effects can be mitigated by interspecific neighbors for Quercus pubescens but exacerbated by interspecific neighbors for Fagus sylvatica.…”
mentioning
confidence: 99%
“…Indeed, the direction of the effect seems to depend on the species composition -and particularly on the species respective strategies in reaction to water stress (Pretzsch et al, 2013;Mas et al, 2024;Jourdan et al, 2020) -as well as on environmental conditions (Grossiord et al, 2014;Pardos et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the effect of tree species richness on the resistance of stands to drought episodes, the literature shows heterogeneous results (Grossiord, 2018). Indeed, the direction of the effect seems to depend on species composition - and particularly on the species respective strategies in reaction to soil water deficit (Pretzsch et al, 2013; Mas et al, 2024; Jourdan et al, 2020) - as well as on environmental conditions (Grossiord et al, 2014; Forrester et al, 2016; Pardos et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of species mixing on drought resistance could result from different mechanisms, such as competitive reduction for water through resource partitioning or facilitation—for instance hydraulic redistribution ( Grossiord 2020 ). Yet, tree species diversity effects on tree drought resistance are not universal and can change in direction and magnitude according to the sites, the species of the composition of the mixture ( Grossiord 2020 ; Grossiord et al 2014b ; Mas et al 2024 ). Indeed, previous studies showed that tree species diversity effect can have positive ( Lebourgeois et al 2013 ; de- Dios-García et al 2015 ; Ruiz-Benito et al 2017 ), neutral ( Grossiord et al 2014b ; Merlin et al 2015 ), or even negative impacts ( Grossiord et al 2014a ; Vitali et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%